Liver Function, Leucocyte, and Blood Pressure Levels with Acute Stroke Functional Outcomes (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Several studies have shown that there is an increase in bilirubin levels, leukocytes, and blood pressure in acute phase strokes. The purpose of this study was to determine the relationship between liver function levels, leucocytes, and blood pressure with the functional outcome of acute stroke. The method was a cross-sectional study with a sample size of 30 people who were selected by consecutive non-random sampling method, clinically proven acute stroke patients, and computed tomography (CT) scan. They were studied at the General Hospital of the Adam Malik Center. Demographic data were analyzed using descriptive statistics. The results showed that all subjects did not differ in terms of demographic characteristics. This study concluds that there is no relation between liver function (total bilirubin, direct bilirubin, indirect bilirubin, serum glutamic oxaloacetic transaminase [AST], serum glutamic pyruvic transaminase [SGPT], alkaline phosphatase [ALP]), leukocytes, and blood pressure with acute stroke functional outcome. The functional outcome in acute hemorrhagic stroke is worse than acute ischemic stroke. Higher levels of liver function, leucocytes, and blood pressure were found in patients with the worse functional outcome though not significantly associated.